Models of drug addiction: Theories and future applications in prevention and treatment. Issue 5 (May 2016) - Palmer, Rohan; McGeary, John
Abstract : Despite advances in addiction research toward greater understanding of etiology, drug use and misuse continue to exact enormous costs on society in the form of treatment costs, medical costs, and lost productivity. This is in large part a result of the exposure of teens and young adults to substances of abuse at a critical time in their development, when their brains have not yet fully developed and are most susceptible to the negative impacts of drug exposure (https://www.drugabuse.gov/news‐events/news‐releases/2015/07/nida‐niaaa‐commentary‐strongly‐supports‐brain‐disease‐model‐addiction ).